Operable invasive breast carcinoma with negative axilla: clinicopathologic and prognostic factors for survival - Díaz, Juan (2015)
OBJECTIVE.- To determine the clinico pathologic picture, recurrence rate and prognostic factors influencing 5-year survival o breast cancer MATERIAL: Retrospective analysis of 39 patients with invasor operable breast cancer with negative axillary nodes who underwent Halsted (n=29) or Patey (n = 10) radical mastectomy between 1966 and 1995. LOCATI0N.Belen Hospital, Trujillo, Peru. RESULTS. Median age was 49 years and the mean time of history was 9,8 months. There were 20 postmenopausal and 19 premenopausal patients. The most frequent symptoms were tumor (100%) and pain (25,6%). The left breast (66,7%) and upper-outer quadrant (48,7%) were the most affected. Infiltrating ductal carcinoma (89,8%) was the most frequent histologic type. The 5-year local and distance recurrence rates were 15,44 and 20,5%, respectively. In the total series, the 5-year actuarial survival rate was 76% Using the univariate analysis, the histologic (p < 0, 01) and nuclear grade (p < 0, 01), blood vessel infiltration (p<O, 05), mitotic index (P < 0,05), peritumoral flbrosis (p < 0,01), multicentricity of tumor (p < 0, 05) and type of mastectomy (p<0, 01) were prognostic factors statistically related with survival. In the Cox' multivariate analysis, significative prognostic factors were the histologic (p = 0,0026) and nuclear (p = 0, 0026) grade, mitotic index (p=0,0191) and type of mastectomy (p = 0,0388). CONCLUSIONS. The histologic and nuclear grade, mitotic index and type of mastectomy were factors that influenced survival of patients with invasor operable breast cancer with negative axillary node and these parameters must be considered in the strafication of patients for systemic adjuvant therapy.